Pembangunan Sistem Informasi Retribusi Pada Usaha Kecil Dan Sektor Usaha Informal Menggunakan Location Based Service Untuk Mendukung Peningkatan Pendapatan Asli Daerah - Erwin Yulianto; Aisyah Nuraeni (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Based on UU No. 9 of 1995, Small Enterprises are small-scale people's economic activities and meet the criteria of net worth of at most two hundred million rupiahs or have annual sales of at most one billion rupiahs and own ownership in the form of individual businesses. The government seeks to empower the business world to improve the growth of the business climate, fostering and developing so that small businesses are able to grow and strengthen themselves into strong and independent businesses. The issue that is developing at this time is not optimal data collection of people who have small businesses from the informal business sector due to the form of their business which is individual and not incorporated so that the lack of Regional Original Income can be obtained by the country. Many small businesses take place outside the formal sector from economic transactions formed by the country, but have the potential to increase business service fees. The informal sector refers to small businesses that are managed by individuals or families but are not equipped with adequate business licensing, red zone violations, reluctance in reporting tax obligations, non-compliance with labor regulations that regulate work contract issues, and have no legal guarantees in dealing with suppliers / customer. This research was compiled to create an information system capable of increasing the sources of Regional Original Income, especially those originating from regional retribution in accordance with UU No. 28 of 2009, namely business service fees which are regional levies as payment for special business services provided and / or provided by regional government for the benefit of individuals or legal entity. The using of the Location Based Service method on the software that is built will be able to handle and coordinate information on small businesses in each region so that it can help local governments to manage Regional Original Income specifically Business Services Retribution optimally.